Analisis Break Even Point (BEP) Usahatani Pembibitan Sapi Potong di Kabupaten Sleman - Shanti Emawati (Universitas Sebelas Maret (UNS), 2007)
The research was conducted to calculate the break even point (BEP) of cattle breeding farm. Research was done from January to May 2007, located in Sleman District. Survey methods was done to collect primary data at the farm level and secondary data from related institution. Purposive sampling was applied to sellect farmers’ respondent. The BEP with calf sales calculation of keeping Simmental, Ongole and Limousine grade cattle were 8, 9 and 7 cows per farmer respectively, which mean that farmers will annually benefited from keeping cattle when the number of cows was larger than those of BEP. Key words : cattle breeding farm, BEP analysis